Comparing High School Sport Specialization Trends Between Division I and Club Collegiate Athletes. (November 2022) - Biese, Kevin M.; Winans, Madeline; Hernandez, Mayrena I.; Schaefer, Daniel A.; Post, Eric G.; Sanfilippo, Jennifer L.; Bell, David R.
Background: Adolescent athletes report that sports specialization improves their ability to receive a collegiate athletics scholarship, though this is not well-understood. The purpose of this study was to examine self-reported trends in high school specialization and influences for sport participation between Division I (D-I) and college-aged club (club) athletes. Hypothesis: There would be no difference in high school sport specialization or sport participation influences between D-I and club athletes. Study Design: Retrospective cross-sectional study. Level of Evidence: Level 3. Methods: A survey included specialization classification (low, moderate, and high) for 9th to 12th grade, age that the athlete started organized sport and his or her collegiate sport, and several influential factors for participation in one's primary high school sport (1 = no influence to 5 = extremely influential). Chi-square analyses were used to compare specialization classifications between groups. Nonparametric tests were used to determine significant differences in age-related variables and influential factors between D-I and club athletes. All analysis were also conducted with boys and girls separately. Results: Participants included 266 D-I (girls, 155; 58%) and 180 club (girls, 122; 68%) athletes. Club athletes were more likely to be classified as low specialization at every grade in high school, and this difference was more pronounced between D-I and club female athletes than male athletes. The number of years an athlete was classified as highly specialized in high school was not different between D-I and club athletes. Club athletes were more influenced by playing with friends than D-I athletes and D-I athletes were more influenced by pursuing a collegiate scholarship than club athletes. Conclusion: High levels of specialization in high school sport may not be necessary for playing at the collegiate level, though some level of specialization in high school might be necessary. Clinical Relevance: Clinicians should advocate for healthy long-term athlete development, which does not support high specialization in high school sports.